TECHNOLOGY-ASSISTED LITERACY STIMULATION: DEVELOPING CHILDREN’S EARLY LITERACY SKILLS - Junita Dwi Wardhani; Febritesna Nuraini; Tri Asmawulan; Isnaini Budi Hastuti; Zulkarnaen (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study aims to examine the impact of technology-based literacy stimulation on developing children’s early literacy skills: learning to read and write. Following the ethical protocol, 133 children of 5-6 years, 8 parents, and 83 kindergarten teachers and 133 children were voluntarily recruited in which seven schools adopting technology-assisted learning were selected. Data were collected through interviews with teachers, observations, and questionnaires. Qualitative content analysis showed that Drawing on qualitative content analysis, the parent participants reported that the use of literacy stimulation was able to increase children’s motivation and independence.